Mothers of children with autistic disorder: perceptions and trajectories - Michele Ebert; Elisiane Lorenzini; Eveline Franco da Silva
Childhood autism is characterized by severe and global impairment in several areas of human development and demands extensive care and dependence on the parents. The objective of this study was to understand the perceptions of mothers of children with autism regarding changes suffered by the child and their trajectories in search of an autism diagnosis. This is an exploratory descriptive study with a qualitative approach conducted with ten participant mothers. Data were collected in 2013 by means of semi-structured interviews. Thematic content analysis produced the following categories: perceptions of mothers as to changes in behaviour and/or development of their children; and trajectories of mothers in search of a diagnosis for their children. After the perception of changes in behaviour/development, mothers face an arduous trajectory of healthcare service utilization.